2020
DOI: 10.1175/jtech-d-19-0119.1
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Cross Validation of Global Ocean Wind Speed Based on Scatterometer Observations

Abstract: Global ocean wind speed observed from seven different scatterometers, namely, ERS-1, ERS-2, QuikSCAT, MetOp-A, OceanSat-2, MetOp-B, and Rapid Scatterometer (RapidScat) were calibrated against National Data Buoy Center (NDBC) data to form a consistent long-term database of wind speed and direction. Each scatterometer was calibrated independently against NDBC buoy data and then cross validation between scatterometers was performed. The total duration of all scatterometer data is approximately 27 years, from 1992… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…A comparison of the mean of NH station values for each sampling date with the mean of satellite values over the Newport region for the corresponding 8-day period shows good agreement (r 2 = 0.34, p < 0.01; Figure 4B). For satellite wind validation, a recent study by Ribal and Young (2020) found that 10-m wind speed and direction measurements from both QuikSCAT and ASCAT match well with in situ 10-m wind speed and direction measurements from buoys located at least 50 km offshore from the National Data Buoy Center (ρ = 0.9593 and 0.9404, respectively), though QuikSCAT had a tendency to overestimate high wind speeds (>15 m/s). This study also compared wind speed measurements from four other satellite scatterometers and found generally good agreement among instruments, so we would expect similar results with these other satellite wind products.…”
Section: Satellite Chlorophyll Concentration and Wind Stressmentioning
confidence: 89%
“…A comparison of the mean of NH station values for each sampling date with the mean of satellite values over the Newport region for the corresponding 8-day period shows good agreement (r 2 = 0.34, p < 0.01; Figure 4B). For satellite wind validation, a recent study by Ribal and Young (2020) found that 10-m wind speed and direction measurements from both QuikSCAT and ASCAT match well with in situ 10-m wind speed and direction measurements from buoys located at least 50 km offshore from the National Data Buoy Center (ρ = 0.9593 and 0.9404, respectively), though QuikSCAT had a tendency to overestimate high wind speeds (>15 m/s). This study also compared wind speed measurements from four other satellite scatterometers and found generally good agreement among instruments, so we would expect similar results with these other satellite wind products.…”
Section: Satellite Chlorophyll Concentration and Wind Stressmentioning
confidence: 89%
“…The U10 and SWH data are from altimeters. 2 The angle between wind direction and MWP. 3 The difference between SST and SSAT.…”
Section: Correlation Of the U10 Errormentioning
confidence: 99%
“…Spaceborne active microwave remote sensors, including radar altimeter, scatterometer, and Synthetic Aperture Radar (SAR), can all be used to retrieve 10-m sea surface wind speed (U10, henceforth) because the Radar Cross-Sections (RCSs) are sensitive to sea surface roughness (SSR) [1], and the SSR is closely correlated to U10. Among these remote sensors, scatterometers have the widest swath and the best overall accuracy (with a typical error of ~1 m/s) [2], making them an irreplaceable data source of U10. Meanwhile, radar altimeters, with a typical error of wind speed of 1.5 m/s (e.g., [3,4]), have a better accuracy in high wind speeds [1] and can provide global coverage of U10 and significant wave height (SWH) data simultaneously, making them also a unique tool for studies in wind-waves (e.g., [5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…used to retrieve 10-m sea surface wind speed (U10, henceforth) because the Radar Cross-Sections (RCSs) are sensitive to sea surface roughness (SSR) [1], and the SSR is closely correlated to U10. Among these remote sensors, scatterometers have the widest swath and the best overall accuracy (with a typical error of ∼1 m/s) [2], making them an irreplaceable data source of U10. Meanwhile, radar altimeters, with a typical error of wind speed of 1.5 m/s (e.g., [3], [4]), have a better accuracy in high wind speeds [1] and can provide global coverage of U10 and significant wave height (SWH) data simultaneously, making them also a unique tool for studies in wind-waves (e.g., [5]- [7]).…”
mentioning
confidence: 99%
“…When establishing the retrieving algorithm, however, the RCSs are usually directly mapped to U10 obtained from other instruments, such as buoys or scatterometers [4]. Although the derived GMFs generally have a good performance in measuring U10 (e.g., [1], [2], [4]), it is noted that U10 is not the only impact factor for SSR. For example, surface ocean currents and atmospheric instability can all have a direct impact on the SSR response to U10 (e.g., [8], [9]), thus impacting the wind retrieval.…”
mentioning
confidence: 99%